Current level of oil hydrocarbons in Russian coastal waters of the Black Sea and and Azov Sea - O. A. Mironov; O. G. Mironov (Юг России: экология, развитие)
Aim. Currently, oil pollution remains one of the primary pollutants of the marine environment. This is especially true for the Black Sea and Azov Sea which experience significant anthropogenic pressure. The study presents the results of two-year monitoring studies of the content of oil hydrocarbons in the surface and bottom horizons of the coastal waters of the Azov-Black Sea regions of Russia.Materials and Methods. The determination of oil hydrocarbons was conducted by infrared spectrometry using a FSM-1201 Fourier spectrophotometer with preliminary transmission of the extracts through a chromatographic column with aluminum oxide. The work was carried out as part of five scientific expeditions (93th, 96th, 100th, 102nd and 105th) of the research vessel, Professor Vodyanitsky, in 2017 and 2018.Results. The general environmental status for this pollutant is characterized as stable, despite in some cases being 3 to 4 times in excess of established standards (MPC). Separate foci of localized oil pollution have been identified and vulnerable areas of the sea coast of southern Russia have been identified. An excess content of petroleum hydrocarbons in the surface layer compared to the bottom layer was noted, which indicates a surface path of entry of petroleum products into sea water.Conclusion. Currently, the coastal waters of the western part of Crimea are most affected by oil, primarily associated with the runoff of European rivers and the peculiarities of the marine hydrological regime, including the Kerch Strait, an area of heavy shipping traffic. The Caucasian coast is less affected by oil pollution than the Crimean. Despite the fact that currently the content of oil hydrocarbons in sea water is far from the quantities dangerous to humans and aquatic organisms, monitoring of this indicator is vital due to the increasing anthropogenic pressure on the recreational zones of the Crimean and Caucasian coasts of the Russian Federation.